Effects of Chronic Pharmacological Treatment on Functional Brain Network Connectivity in Patients with Schizophrenia. (January 2021) - Lin, Xiao; Deng, Jiahui; Dong, Guangheng; Li, Suxia; Wu, Ping; Sun, Hongqiang; Liu, Lin; Shi, Jie; Fan, Yong; Lu, Lin; Li, Peng
Highlights: Patients with schizophrenia exhibited a significant decrease in FC of the cingulate gyrus in the DMN Decreased FC of the cingulate gyrus was negatively correlated with symptom severity Clinical improvements were observed after 6 weeks of treatment Increased FC of the cingulate gyrus in the DMN and inferior parietal lobule in the ECN was noted Increased FC of the inferior parietal lobule was correlated with symptom improvement Abstract: Schizophrenia is characterized by the dysfunction of various brain networks. Previous studies suggested that pharmacological treatments for schizophrenia induce functional changes in localized brain regions. However, the effects of antipsychotic treatments on brain networks associated with symptom improvement are still elusive. The elucidation of antipsychotic-induced functional brain changes is essential for the development of biologically informed treatment strategies. Forty-five healthy controls and 44 patients with schizophrenia underwent resting-state fMRI scans at baseline. The patients underwent a second scan after 6 weeks of antipsychotic treatment. At baseline, patients exhibited a significant decrease in functional connectivity of the cingulate gyrus in the default mode network compared to healthy controls, and this decrease was negatively correlated with symptom severity. Clinical improvements were observed after 6 weeks treatment, accompanied by an increase in functional connectivity of the cingulate gyrus in the default mode network and the inferior parietal lobule in the executive control network. The changes in functional connectivity of the inferior parietal lobule were significantly correlated with symptom improvement. These longitudinal neuroimaging findings suggest that schizophrenia might be an outcome of the disruption of the optimal balance of brain networks, and reestablishing this balance through antipsychotic treatment may result in clinical symptom improvement.